The shadow lines - Ghosh, Amitav. 1956- (New Delhi : Ravi Dayal ; Delhi, 1998)
Opening in Calcutta in the 1960s, Ghosh's radiant second novel follows two families. one English, one Bengali, as their lives intertwine in tragic and comic ways. The narrator, Indian-born and English educated, traces events back and forth in time, through years of Bengali partition and violence, observing the ways in which political events invade private lives.
Keywords: Boys -- Fiction; British -- India -- Fiction; Kolkata (India) -- Fiction; India -- Fiction